WASP-169, WASP-171, WASP-175, and WASP-182: three hot Jupiters and one bloated sub-Saturn mass planet discovered by WASP-South. Issue 2 (23rd August 2019) - Nielsen, L D; Bouchy, F; Turner, O D; Anderson, D R; Barkaoui, K; Benkhaldoun, Z; Burdanov, A; Cameron, A Collier; Delrez, L; Gillon, M; Ducrot, E; Hellier, C; et al.
ABSTRACT: We present the discovery of four new giant planets from the Wide Angle Search for Planets-South (WASP-South), three hot Jupiters and one bloated sub-Saturn mass planet: WASP-169b, WASP-171b, WASP-175b, and WASP-182b. Besides the discovery photometry from WASP-South we use radial velocity measurements from CORALIE and HARPS and follow-up photometry from EulerCam, TRAPPIST-North and -South, and SPECULOOS. WASP-169b is a low-density Jupiter ($M=0.561 ± 0.061\, {M_{\rm Jup}}, \ R=1.304^{+0.150}_{-0.073}\, {R_{\rm Jup}}$ ) orbiting a V = 12.17 F8 subgiant in a 5.611 d orbit. WASP-171b is a typical hot Jupiter ($M=1.084 ± 0.094\, {M_{\rm Jup}}, \ R=0.98^{+0.07}_{-0.04}\, {R_{\rm Jup}}$, P = 3.82 d) around a V = 13.05 G0 star. We find a linear drift in the radial velocities of WASP-171 spanning 3.5 yr, indicating the possibility of an additional outer planet or stellar companion. WASP-175b is an inflated hot Jupiter ( M = 0.99 ± 0.13 M Jup, R = 1.208 ± 0.081 R Jup, P = 3.07 d) around a V = 12.04 F7 star, which possibly is part of a binary system with a star 7.9 arcsec away. WASP-182b is a bloated sub-Saturn mass planet ( M = 0.148 ± 0.011 M Jup, R = 0.850 ± 0.030 R Jup ) around a metal-rich V = 11.98 G5 star ([Fe/H] = 0.27 ± 0.11). With an orbital period of P = 3.377 d, it sits right in the apex of the sub-Jovian desert, bordering the upper and lower edge of the desert in both the mass–period and radius–period plane. WASP-169b, WASP-175b, and WASP-182b are promising targets for atmospheric characterization through transmission spectroscopy, with expected transmission signals of 121, 150, and 264 ppm, respectively.